Not Enough Fat: Mouse Models of Inherited Lipodystrophy - Le Lay, Soazig; Magré, Jocelyne; Prieur, Xavier (Frontiers in Endocrinology, 2022)
Lipodystrophies belong to the heterogenous group of syndromes in which the primary defect is a generalized or partial absence of adipose tissue, which may be congenital or acquired in origin. Lipodystrophy should be considered in patients manifesting the combination of insulin resistance (with or without overt diabetes), dyslipidemia and fatty liver. Lipodystrophies are classified according to the etiology of the disease (genetic or acquired) and to the anatomical distribution of adipose tissue (generalized or partial). The mechanism of adipose tissue loss is specific to each syndrome, depending on the biological function of the mutated gene. Mice models, together with cellular studies have permitted clarification of the mechanisms by which human mutations deeply compromise adipocyte homeostasis. In addition, rodent models have proven to be crucial in deciphering the cardiometabolic consequences of the lack of adipose tissue such as NAFLD, muscle insulin resistance and cardiomyopathy. More precisely, tissue-specific transgenic and knockout mice have brought new tools to distinguish phenotypic traits that are the consequences of lipodystrophy from those that are cell-autonomous. In this review, we discuss the mice models of lipodystrophy including those of inherited human syndromes of generalized and partial lipodystrophy. We present how these models have demonstrated the central role of white adipose tissue in energetic homeostasis in general, including insulin sensitivity and lipid handling in particular. We underscore the differences reported with the human phenotype and discuss the limit of rodent models in recapitulating adipose tissue primary default. Finally, we present how these mice models have highlighted the function of the causative-genes and brought new insights into the pathophysiology of the cardiometabolic complications associated with lipodystrophy.